Investigating the experience of stress and coping in elite athletes - Barlow, D. (Bournemouth University, 2023)
Stress and coping are both a part of the human experience, affecting every area of life. In elite sporting environments, stress is often magnified with the expectations and demands that are placed upon athletes, therefore effective coping mechanisms are vital to an athlete`s performance and well-being. This study investigates the experiences of stress and coping among elite athletes. Previous research has split stress sources (in athletes) into three categories; performance, organisational and personal. Studies have tended to focus on the three stressor categories as individual phenomena; therefore, this study aims to explore the sources of stress as a group to investigate the effect they have on each other. Seven athletes (n= 5 male, n= 2 female) from six different sports (n= 2 football, n=1 Rugby Union, n= 1, hockey, n=1 cycling, n = 1 dance n = 1 fell running) participated in the study. A qualitative methodology was selected, specifically semi structured interviews lasting approximately1 hour. This was selected to obtain rich, in-depth insight on how athletes cope with the stressors they face and the impact the stressors and coping mechanisms have on them. The results were then analysed using thematic analysis and have been presented as such in the results and discussion section. The findings revealed that the standard three-category stress model is insufficient for usage within academic research. This is because it doesn't allow for any interaction between the three categories of stress sources (performance, organisational and personal). A new model evidencing the interactions between the sources of stress was proposed. This would enable the sources of stress to inter-connect whilst still keeping their independence as stand-alone stressors. However, as this model was proposed from a small data sample, further research will be required to assess the effectiveness of this emerging new model in the sporting context.